Maternal History of Adverse Experiences and Posttraumatic Stress Disorder Symptoms Impact Toddlers’ Early Socioemotional Wellbeing: The Benefits of Infant Mental Health-Home Visiting - Ribaudo, Julie; Lawler, Jamie M.; Jester, Jennifer M.; Riggs, Jessica; Erickson, Nora L.; Stacks, Ann M.; Brophy-Herb, Holly; Muzik, Maria; Rosenblum, Katherine L. (Frontiers in Psychology, 2022)
Abstract Background: The present study examined the efficacy of the (Blinded for Review) infant mental health treatment to promote the socioemotional wellbeing of infants and young children. Science illuminates the role of parental “co-regulation” of infant emotion as a pathway to young children’s capacity for self-regulation. The synchrony of parent-infant interaction begins to shape the infant’s own nascent regulatory capacities. Parents with a history of childhood adversity, such as maltreatment or witnessing family violence, and who struggle with symptoms of post-traumatic stress may have greater challenges in co-regulating their infant, thus increasing the risk of their children exhibiting social and emotional problems such as anxiety, aggression, and depression. Early intervention that targets the infant-parent relationship may help buffer the effect of parental risk on child outcomes. Methods: Participants were 58 mother-infant/toddler dyads enrolled in a longitudinal randomized control trial testing the efficacy of a relationship-based (blinded for review) infant mental health treatment model. Families were eligible based on child age (< 24 months at enrollment) and endorsement of at least two of four socio-demographic factors commonly endorsed in community mental health settings: elevated depression symptoms, three or more Adverse Childhood Experiences (ACEs) parenting stress, and/or child behavior or development concerns. This study included dyads whose children were born at the time of study enrollment and completed 12-month post-baseline follow-up visits. Parents reported on their own history of ACEs and current PTSD symptoms, as well as their toddler’s socioemotional development (e.g., empathy, prosocial skills, aggression, anxiety, prolonged tantrums). Results: Maternal ACEs predicted more toddler emotional problems through their effect on maternal PTSD symptoms. Parents who received (blinded for review) treatment reported more positive toddler socioemotional wellbeing at follow-up relative to the control condition. The most positive socioemotional outcomes were for toddlers of mothers with low to moderate PTSD symptoms who received (blinded for review) treatment.